CORPORATE VALUES: GOVERNANCE, RISK, COMPLIANCE (GRC) AND LEVERAGE - Muslih, Muhamad; Meynisa, Ambel (JRAK, 2024)
Integrating Islamic banking into Indonesia’s broader financial system could provide valuable insights into the challenges and opportunities associated with traditional banking practices with Sharia-compliant values. This research examined the effect of Governance, Risk, Compliance, and leverage on the corporate value of Islamic Commercial Banks in Indonesia from 2018-2022, with size, age, and profitability as control variables. The research utilized panel data regression on 11 purposively sampled banks, and it found that GRC and leverage significantly affected corporate value simultaneously. Moreover, the board of directors and Sharia Supervisory Board negatively affected corporate value, while the audit committee and leverage had a positive effect. Corporate size and age significantly affected corporate value, whereas profitability did not. The research underscored the importance of GRC and leveraged in determining corporate value and calls for additional research to assist the investor in making informed decisions and evaluating potential investments in the Islamic financial sector.